Viewing the American West as a Chicana in China. Issue 1 (6th December 2021) - Montoya, María E
Abstract: In both scholarly work and popular imagination, the American West is the final destination of migrant from Europe and Mexico. The stories of those migrants, however, obscure the first migration (12, 000 BP) from Asia into North America. That migration across the now-submerged land bridge of Beringia ended humanity's millennia-long journey across the globe that originated in Africa more than 50, 000 years earlier. Using two examples, this essay reflects on how the Asian origins of the first Americans have been transformed into myths that conceal humanity's migratory nature. First, in Chinese Communist propaganda, those origins are transformed into the myth of Peking Man as a branch of humanity originating in China rather than Africa. Second, in the writing of Rudolfo Anaya, those Asian origins are transformed into the myth of homogenous "Brown Brothers" united against white imperialists. Rather than rely on a myth of racial unity in some original homeland, this essay urges reliance on the shared experience of migration and home-making in hostile environments as the true source of our common humanity. Anaya's Golden Carp, symbol of the life-giving fierce of water in an arid environment, captures this common human predicament stretching from Tibet and Xinjiang to New Mexico, epitomizing the American West as the place where humanity has been reunited, the home to the last wanderers of the human race.